2007
DOI: 10.1016/j.cbd.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular acidosis in rodents exposed to cadmium is caused by adaptation of the tissue rather than an early effect of toxicity

Abstract: Proton (1 H) Nuclear Magnetic Resonance (NMR) spectroscopy was used to investigate the biochemical response of bank voles and wood mice (two wild rodent species that are frequently found on metal-contaminated sites) to chronic cadmium (Cd) insult. Similar effects, in terms of both metabolic changes (consistent with cellular acidosis) and induced metallothionin (MT) production were observed in all animals. These changes appeared to be an adaptation of the liver to toxic insult rather than onset of a toxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These studies have allowed the identification of some metabolites (acetilspermidine, glucose, histidine, l-methylhistidine, mannose) that can be used as biomarkers for Cu, Cd and Zn pollution in various animal species (Bundy et al 2004(Bundy et al , 2008Taylor et al 2009;Guo et al 2009). In rats, in addition to the changes in amino acid and sugar contents, a further abnormal metabolome composition has been observed as a result of Cd and Cu intake (Jones et al 2007;Lei et al 2008), and changes in lipid metabolism under high levels of As have also been observed (Griffin et al 2000). A tendency to increase the production of AMP, ADP and N-a-methylhistidine, and to generate an imbalance in metabolites related to energetics by reducing ATP levels has been reported in Lumbricus rubellus (Bundy et al , 2008.…”
Section: Hypoxiamentioning
confidence: 98%
See 1 more Smart Citation
“…These studies have allowed the identification of some metabolites (acetilspermidine, glucose, histidine, l-methylhistidine, mannose) that can be used as biomarkers for Cu, Cd and Zn pollution in various animal species (Bundy et al 2004(Bundy et al , 2008Taylor et al 2009;Guo et al 2009). In rats, in addition to the changes in amino acid and sugar contents, a further abnormal metabolome composition has been observed as a result of Cd and Cu intake (Jones et al 2007;Lei et al 2008), and changes in lipid metabolism under high levels of As have also been observed (Griffin et al 2000). A tendency to increase the production of AMP, ADP and N-a-methylhistidine, and to generate an imbalance in metabolites related to energetics by reducing ATP levels has been reported in Lumbricus rubellus (Bundy et al , 2008.…”
Section: Hypoxiamentioning
confidence: 98%
“…It provides the phenotypical response at the metabolic level in a particular environmental circumstance. Moreover, it is also a powerful tool to monitor the phenotypic variability of one genotype in response to environmental changes in drought (Fumagalli et al 2009), nutrient availability (Hirai et al 2004(Hirai et al , 2005, pollutants (Jones et al 2007;Bundy et al 2008), salinity (Fugamalli et al 2009), temperature (Michaud and Delinger 2007) and biotic interactions ), among other ecological factors. These studies are especially adequate in plants because metabolomic studies enable the simultaneous analysis of primary compounds together with secondary compounds, which have a defensive and protective function.…”
Section: Introductionmentioning
confidence: 99%
“…No effects were seen for wood mice (Apodemus sylvaticus) exposed to the same arsenic levels, indicating a clear species sensitivity difference (Griffin et al 2001). Jones et al (2007) carried out a similar comparative study, again with cadmium, comparing longer-term (3 months as opposed to 14 days) chronic exposure to C. glareolus and A. sylvaticus. They noted similar metabolic differences to those observed by Griffin et al (2000a, b), and that C. glareolus accumulated more cadmium and had a more pronounced response than A. sylvaticus.…”
Section: Laboratory Studies Of Terrestrial Organismsmentioning
confidence: 99%
“…For robust ecological risk assessment of mixtures there is a need to not only describe the results of exposure to chemical mixtures but also to understand the underlying biological mechanisms. Highthroughput, molecular biology techniques, such as -omics based methods, have recently been demonstrated to be valuable for understanding the mechanisms of toxicity (Viant et al 2003;Jones et al 2007;Jones et al 2008). Metabolomics in particular has several advantages in this respect.…”
Section: Introductionmentioning
confidence: 99%